Representasi pustakawan dalam budaya populer: Analisis semiotika Film Doctor Strange (2016) - Yohanes Setiawan (FPPTI Jawa Tengah, 2025)
With the advancement of technology and information, librarians play a crucial role as guardians of knowledge and information. Librarians need to enhance their skills in order to assist users in fulfilling their knowledge and information needs. This article aims to explore the representation of librarians in the film Doctor Strange, which reflects the reality of contemporary librarianship. The analysis in this study employs Roland Barthes' model of semiotics and the theory of representation to uncover both the denotative and connotative meanings of the librarian character. The findings reveal that Wong is portrayed as a skilled, trustworthy, and highly responsible librarian in managing and safeguarding knowledge and information. The role of the librarian is shown to be complex—not limited to administrative tasks, but extending further as a gatekeeper of information and knowledge.